A bibliometric review of perceptions of the built environment supported by multi-source data - Tingjin Wu; Jinxiu Wu; Yanxiang Yang; Wei Dong (Journal of Asian Architecture and Building Engineering)
Information and digital technologies have revolutionized research methodologies for measuring people’s perceptions of built environments. Vast amounts of urban data can now be collected, providing more accurate and intuitive presentation and analysis tools. This enhances the research on the built environment from a human-centered perspective. In this paper, with the help of the CiteSpace knowledge map analysis tool, manual deep intervention was combined with clustering and stratified sampling of literature information to identify hot topics and research trends. The results demonstrate that there are two new perspectives. The first is the up-bottom urban/group perspective, specifically a holistic study of group perceptions by large-scale data, represented by big data, with technologies such as artificial intelligence. The second is the bottom-up humanistic/individual perspective, which accurately examines individual perceptions through physiological data based on ergonomics techniques, psychological, and other small-scale data. Furthermore, these two perspectives are interconnected, indicating a cross-trend in both directions. By bridging the gap between subjective perception and the real-world environment, integrating multi-source data offers a more precise and efficient foundation for thoroughly evaluating the built environment, which would help us better understand the built environment and satisfy the users’ demands in the research and practice of urban design.